A self-indicating and antibacterial gelatine–chitosan blended hydrogel enabling real-time quality control and sustained bioactive agent delivery. Issue 17 (17th April 2023) - Lai, Wing-Fu; Reddy, Obireddy Sreekanth; Law, Lucy; Wu, Haicui; Wong, Wing-Tak
Abstract : Hydrogels are one type of materials that are widely exploited for bioactive agent delivery, partly owing to their high biocompatibility and low toxicity. Abstract : Hydrogels are one type of materials that are widely exploited for bioactive agent delivery, partly owing to their high biocompatibility and low toxicity. When hydrogels are used as carriers, their performance in agent loading and sustained agent release are predominately determined by the gel structure, which can be largely affected by variations during gel preparation. Till now, effective and easy methods to enable monitoring of such variations in real time have been lacking, making quality control of the generated gel-based carrier technically challenging. To address this technical gap, in this study we take advantage of the clusteroluminogenic properties of gelatine and chitosan to generate a crosslinked blended hydrogel which not only shows intrinsic antibacterial properties and high tunability in delivery performance but also shows a self-indicating capacity to enable quality control during hydrogel preparation. Upon fitting the curves of agent release into different kinetic models, the release profiles of the agent-loaded gels have been found to follow the Higuchi model well, with the non-Fickian mechanism being the major mechanism of the release process. Along with their high efficiency in agent loading, our gels warrant further exploitation for use in bioactive agent delivery and related biomedical applications.